2015
DOI: 10.4139/sfj.66.534
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Adhesion of Cu/glass Stacks using ZnO Thin Films Deposited by Chemical Solution Methods and Its Formation Conditions

Abstract: 塗布法によって堆積した ZnO 薄膜を用いた Cu / ガラス構造の密着性向上ならびにその形成条件の検討 渡邉 満洋 a,* ,小池 光海 b ,近藤 英一 a a 山梨大学 大学院総合研究部 (〒 400-8511 山梨県甲府市武田 4-3-11) b 山梨大学 工学部 (〒 400-8511 山梨県甲府市武田 4-3-11)After zinc oxide (ZnO) thin films were deposited using chemical solution methods such as sol-gel method and metal organic decomposition, the deposited ZnO thin films were used as a precursor promoting adhesion in Cu/glass stack systems. Transparent ZnO thin films were deposited on a borosilicate glass substrate using chemical solution methods. X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is found that this adhesion enhancement is not influenced by the kind of glass substrate. The influence of the kind of ZnO layer on adhesion strength was examined [30,31]. ZnO layer was fabricated by sol-gel method, metal organic decomposition (MOD), and supercritical fluid chemical deposition (SFCD), and we investigated whether these ZnO layers improve the adhesion of Cu/glass stacks.…”
Section: Znmentioning
confidence: 99%
“…It is found that this adhesion enhancement is not influenced by the kind of glass substrate. The influence of the kind of ZnO layer on adhesion strength was examined [30,31]. ZnO layer was fabricated by sol-gel method, metal organic decomposition (MOD), and supercritical fluid chemical deposition (SFCD), and we investigated whether these ZnO layers improve the adhesion of Cu/glass stacks.…”
Section: Znmentioning
confidence: 99%